EDUCATIONAL INNOVATION THROUGH MOSQUES AND TAKLIM ASSEMBLY: A LIFELONG LEARNING MODEL FOR MUSLIM COMMUNITIES - Ahmad Zainuddin; M. Tahir; Wahdiansyah Wahdiansyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Mosques and Islamic study groups are two important institutions in Islamic education that have roots dating back to the time of the Prophet Muhammad (peace be upon him). However, in contemporary practice, their function is often limited to routine lectures without any innovation in curriculum or methods. This study aims to explore the transformation of mosque-based education and Islamic study groups through a library approach by examining primary sources (the Qur'an, hadith), academic literature, and recent research, particularly in East Kalimantan. The results of the study indicate that mosques and Islamic study groups can play a role as centers of lifelong learning through four main strategies: (1) expanding access to inclusive education for all groups; (2) developing a contextual curriculum that includes religious, digital, and socio-economic literacy; (3) implementing a blended learning model that combines face-to-face with digital platforms; and (4) strengthening multi-stakeholder partnerships with universities, the government, and the community. The normative basis of QS. Al-'Alaq [96]:1, QS. At-Taubah [9]:18, and the Prophet's hadith regarding the obligation to seek knowledge emphasizes the relevance of this innovation to Islamic teachings. With the support of higher education institutions such as UINSI Samarinda, mosques and Islamic study groups in East Kalimantan have the potential to become centers of adaptive, moderate, and sustainable community-based Islamic education.